2018
DOI: 10.3389/fnagi.2018.00381
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Education May Be Sufficient to Moderate a Memory-Hippocampal Relationship

Abstract: According to the cognitive reserve theory, intellectual stimuli acquired during life can prevent against developing cognitive impairment. The underlying cognitive reserve mechanisms were underexplored in low-educated individuals. Because episodic memory impairment due to hippocampal dysfunction is a key feature of Alzheimer’s dementia (AD), we sought to look at a possible cognitive reserve mechanism by determining whether few years of education moderated the relationship between the hippocampal volumes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
(49 reference statements)
1
21
0
Order By: Relevance
“…However, previous studies of normal aging population found mixed or contradicting results in how educational attainment or proxies of CR alter the association between GMV and cognitive functioning. For example, two studies specifically showed that age‐related GMV variation was positively associated with cognitive functions and such a relationship was stronger in higher CR elderly individuals . Similar or null results were reported in other studies examining the moderating role of CR, showing a stronger association between pathological impact and cognitive functions in higher CR elderly .…”
Section: Introductionmentioning
confidence: 51%
“…However, previous studies of normal aging population found mixed or contradicting results in how educational attainment or proxies of CR alter the association between GMV and cognitive functioning. For example, two studies specifically showed that age‐related GMV variation was positively associated with cognitive functions and such a relationship was stronger in higher CR elderly individuals . Similar or null results were reported in other studies examining the moderating role of CR, showing a stronger association between pathological impact and cognitive functions in higher CR elderly .…”
Section: Introductionmentioning
confidence: 51%
“…Also, further analyses of elderly subgroups from LMIC environments stratified according to different levels of educational attainment may reveal other meaningful findings regarding to hippocampal volume variations as a function of number of years of education. For instance, one recent MRI investigation in an elderly sample combining subjects with or without cognitive impairment recruited in a similar LMIC environment showed a significant interaction between larger hippocampal volumes and higher educational attainment predicting better episodic memory performance (Resende et al., 2018). Analyses of HSVs in subsamples of elderly subjects with low educational attainment should also evaluate possible relationships with WMH, in order to verify whether hippocampal tissue may be more prominently affected by microvascular pathology specifically in such elderly subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have attempted to define the best indicators of CR, considering measures as varied as education, leisure activities and life experiences. The hypothesis is that all of these experiences would model the cognitive networks and enable individuals to cope with brain pathology more or less successfully (Resende et al, 2018).…”
Section: The Brain Reserve Biologymentioning
confidence: 99%